Design and implementation of an 85-kHz Bidirectional Wireless Charger - Triviño-Cabrera, Alicia (My University, 2018)
Bidirectional wireless chargers will facilitate the seamless adoption of the V2G technology. When compared with unidirectional systems, developing a bidirectional wireless charger for an EV poses some new challenges. This paper presents some of the technological challenges (mainly related to the power converters) that we have addressed when building a bidirectional wireless charger. In particular, we have built a 3.7 kW bidirectional prototype working at 85 kHz. Experimental results for both power flows demonstrate the validity of the design.
Keywords: Vehículos eléctricos; Wireless power transfer; Electric vehicle; Bidirectional